PEMODELAN MATEMATIKA PENYEBARAN PERILAKU MEROKOK BERDASARKAN FAKTOR EKONOMI DAN FAKTOR PSIKOLOGI - Elinora Naikteas Bano; Sulasri Suddin; Leonardus Frengky Obe; Desi Marida Babis (Saintek Lahan Kering, 2021)
Smoking is the activity of burning tobacco then sucking the smoke and releasing it back through the mouth. This study examines the spread of smoking behavior based on economic factors and psychological factors. This model divides the population into 4 subpopulations, namely potential smoker , Beginner smoker , Smoker subpopulation and recovery subpopulation The stability of the smoking-free equilibrium point is obtained by linearizing the equation to obtain the Jacobian matrix and then the eigenvalues will be obtained. The basic reproduction number which is the threshold for the spread of smoking behavior where smoking behavior will disappear if Ro < 1 and will be endemic when Ro > 1.